2010
DOI: 10.2320/matertrans.p-m2010803
|View full text |Cite
|
Sign up to set email alerts
|

Springback Characteristics of Magnesium Alloy Sheet AZ31B in Draw-Bending

Abstract: In this study, we carried out a two-dimensional draw-bending test on an AZ31B magnesium alloy sheet at various forming temperatures and blank holding forces, and the springback characteristics of the Mg alloy sheet were systematically examined. The amount of springback decreased with increasing temperature and blank holding force. The decrease in the amount of springback caused by the increase in temperature was much larger than that caused by the increase in blank holding force, which indicated that increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…Bruni et al [2] studied the effect of reducing springback as the punch radius decreases with warm air bending of the magnesium alloy sheet. Hama et al [3] confirmed that the springback is reduced as the temperature increases in draw bending of the magnesium alloy sheet. Nguyen et al [4] studied the material constitutive equation for springback prediction at various temperatures in V-bending process of magnesium alloy sheet.…”
Section: Introductionmentioning
confidence: 54%
“…Bruni et al [2] studied the effect of reducing springback as the punch radius decreases with warm air bending of the magnesium alloy sheet. Hama et al [3] confirmed that the springback is reduced as the temperature increases in draw bending of the magnesium alloy sheet. Nguyen et al [4] studied the material constitutive equation for springback prediction at various temperatures in V-bending process of magnesium alloy sheet.…”
Section: Introductionmentioning
confidence: 54%
“…The press forming of Mg alloy sheets has recently attracted attention because it can further expand the use of Mg alloys for structural components. Many studies on the press forming of Mg alloy sheets (Kim et al, 2008;Kaneko and Sugamata, 2004;Doege and Droder, 2001;Lee et al, 2002Lee et al, , 2007Bruni et al, 2006;Hama et al, 2010a) have been carried out, and various components are manufactured by press forming, such as the housing of laptop computers and cellular phones, and automobile body structures.…”
Section: Introductionmentioning
confidence: 99%
“…Hamasaki et al 22) investigated an appropriate definition of apparent elastic modulus during unloading suitable for accurate springback predictions in cold-rolled copper alloy sheets. The present authors 23) conducted loading-unloading tests in an AZ31 magnesium (hereafter termed as Mg) alloy sheet under various loading paths and showed that the nonlinearity during unloading is different depending on loading paths. We also depicted that the nonlinear deformation during unloading in the Mg alloy sheet can be predicted well using a crystal plasticity finiteelement simulation.…”
Section: Introductionmentioning
confidence: 90%
“…The apparent elastic modulus E a was calculated by linearly approximating the whole unloading curve using the least square method. The instantaneous gradient dσ/dε was calculated using two data points for every 100 successive points 23) or a strain increment of approximately 6.67 × 10 Q ae and Q a are schematically shown in Fig. 1.…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation